2022
DOI: 10.1007/s11255-022-03114-7
|View full text |Cite
|
Sign up to set email alerts
|

Kidney failure, CKD progression and mortality after nephrectomy

Abstract: Purpose This study tested the hypothesis that progression of chronic kidney disease (CKD) is less aggressive in patients whose primary cause of CKD was nephrectomy, compared with non-surgical causes. Methods A sample of 5983 patients from five specialist nephrology practices was ascertained from the Queensland CKD Registry. Rates of kidney failure/death were compared on primary aetiology of CKD using multivariable Cox proportional hazards models. CKD progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, even in this elective setting, the risk of surgically induced CKD should not be overlooked, given the adverse sequelae and the increased risk of mortality caused by CKD [2] , [6] . Interestingly, the prognostic impact of medical versus surgical CKD has been debated [6] , as CKD after nephrectomy was associated with a tangible risk of kidney failure and death, comparable with other major causes of CKD [21] . In this regard, a landmark study by Wu et al [22] using a competing-risk analysis showed significantly reduced non–renal cancer–related survival for surgically induced CKD with eGFR <45 ml/min/1.73 m 2 compared with no-CKD or surgically induced CKD with eGFR 45–60 ml/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, even in this elective setting, the risk of surgically induced CKD should not be overlooked, given the adverse sequelae and the increased risk of mortality caused by CKD [2] , [6] . Interestingly, the prognostic impact of medical versus surgical CKD has been debated [6] , as CKD after nephrectomy was associated with a tangible risk of kidney failure and death, comparable with other major causes of CKD [21] . In this regard, a landmark study by Wu et al [22] using a competing-risk analysis showed significantly reduced non–renal cancer–related survival for surgically induced CKD with eGFR <45 ml/min/1.73 m 2 compared with no-CKD or surgically induced CKD with eGFR 45–60 ml/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 99%